2006
DOI: 10.1111/j.1525-1497.2006.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of teaching clinical skills using virtual and live standardized patients

Abstract: Improvements in performance and diagnostic ability were equivalent between the groups and participants rated VP and SP cases equally. Including well-designed VPs has a potentially powerful and efficient place in clinical skills training for practicing health care workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(135 citation statements)
references
References 15 publications
8
125
1
1
Order By: Relevance
“…Computer or web applications are a great asset for learning basic knowledge (Chumley-Jones et al 2002). Virtual patients are effective for teaching clinical reasoning and patient management in non-dynamic situations (Triola et al 2006), and may be the modality of choice for these domains (Cook & Triola 2009), although a recent meta-analysis showed no difference with other, non-computer instruction (Cook et al 2010). Virtual worlds have shown promise in developing teamwork and crisis management skills, and have proven, in one pilot study, equally as effective as simulated clinical immersion (Youngblood et al 2008).…”
Section: Id In Simulation and The Outcomes Of Learningmentioning
confidence: 99%
“…Computer or web applications are a great asset for learning basic knowledge (Chumley-Jones et al 2002). Virtual patients are effective for teaching clinical reasoning and patient management in non-dynamic situations (Triola et al 2006), and may be the modality of choice for these domains (Cook & Triola 2009), although a recent meta-analysis showed no difference with other, non-computer instruction (Cook et al 2010). Virtual worlds have shown promise in developing teamwork and crisis management skills, and have proven, in one pilot study, equally as effective as simulated clinical immersion (Youngblood et al 2008).…”
Section: Id In Simulation and The Outcomes Of Learningmentioning
confidence: 99%
“…4,5 Virtual patient technology has been used by educators throughout the health sciences to develop required knowledge and skills. 4,[6][7][8] Virtual patients simulate real clinical scenarios and allow learners to emulate the roles of healthcare providers by obtaining patient information and making diagnostic and therapeutic decisions. 9 Virtual patients offer educators the opportunity to assess students' decision-making skills regarding course content in a safe, high-fidelity environment, while allowing students to succeed, err, and learn individually.…”
Section: Introductionmentioning
confidence: 99%
“…Once developed, they can be Murphy S, Imam B, Whitehouse L MedEdPublish https://doi.org/10.15694/mep.2016.000107 Page | 5 repeatedly utilized for large numbers of students at little further cost (Bateman et al, 2013) and are easy to administer compared to the resource intensive process of scheduling and training standardized patients, and provide known and consistent content for each student who views them. A study by Triola et al (2006) showed little difference in the outcomes of virtual patients and standard patients in terms of post -encounter performance or perceived effectiveness of the experience by students.…”
Section: Tip #8: Consider Cost-effectivenessmentioning
confidence: 99%